Kredytowanie obszarów wiejskich na przykładzie regionu zamojskiego - Żmija, Janusz; Szafrańska, Monika (Results of Credits in Rural Areas of Zamosc Region, 2006)
Cheap loans, mostly for investments, allowed modernization and restructurisation of farms, leading to more rational utilization of production factors in their disposal. This allowed changes in agricultural production leading to lowering costs and increasing efficiency of farms. For some of the farms cheap credits were the only chance for investments and production continuity. It has also a very important social perspective, as the abounding agriculture production increases the level of unemployment in rural areas and problems connected with land cultivation.This type of credits created the increase of economic activities such as buying machines and agricultural equipment, construction materials and creating new jobs.To sum up, the crediting of rural areas favoures the processes of creating economically strong entities that may compete on a free market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 570-576